Multiple loci on 8q24 associated with prostate cancer susceptibility. - Al Olama, A; Kote-Jarai, Z; Giles, G; Guy, M; Morrison, J; Severi, G; Leongamornlert, D; Tymrakiewicz, M; Jhavar, S; Saunders, E; Hopper, J; Southey, M; et al. (2009)
Previous studies have identified multiple loci on 8q24 associated with prostate cancer risk. We performed a comprehensive analysis of SNP associations across 8q24 by genotyping tag SNPs in 5,504 prostate cancer cases and 5,834 controls. We confirmed associations at three previously reported loci and identified additional loci in two other linkage disequilibrium blocks (rs1006908: per-allele OR = 0.87, P = 7.9 x 10(-8); rs620861: OR = 0.90, P = 4.8 x 10(-8)). Eight SNPs in five linkage disequilibrium blocks were independently associated with prostate cancer susceptibility.